2016
DOI: 10.1111/cpr.12287
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐137 suppresses tongue squamous carcinoma cell proliferation, migration and invasion

Abstract: These results indicate that miR-137 acted as a tumour suppressor in TSCC by targeting SP1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 61 publications
1
41
0
Order By: Relevance
“…miR-137 hypermethylation leads to its inhibition in many tumors, such as colorectal cancer, pancreatic cancer, and endometrial cancer [29][30][31] . Functional analysis has indicated that miR-137 can inhibit cell proliferation, cell cycle arrest and apoptosis, cell migration and invasion, and affect chemoresistance [32][33][34][35][36] . For example, miR-137 overexpression sensitized resistant colon cancer cells to oxaliplatin 20 .…”
Section: Discussionmentioning
confidence: 99%
“…miR-137 hypermethylation leads to its inhibition in many tumors, such as colorectal cancer, pancreatic cancer, and endometrial cancer [29][30][31] . Functional analysis has indicated that miR-137 can inhibit cell proliferation, cell cycle arrest and apoptosis, cell migration and invasion, and affect chemoresistance [32][33][34][35][36] . For example, miR-137 overexpression sensitized resistant colon cancer cells to oxaliplatin 20 .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous, short (~22 nucleotide), noncoding, single‐stranded RNAs that can regulate translational inhibition or mRNA degradation by binding to the 3′ untranslated regions (3′‐UTRs) of some specific mRNAs . Studies have shown that miRNAs participate in a range of pathological and physiological processes, including cell proliferation, differentiation, apoptosis, organ development, and tumor oncogenesis . In particular, numerous studies have published that miRNAs play critical roles in osteogenic differentiation .…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, evidence has suggested that Sp1 may be involved in a variety of cellular processes, including cell growth, survival, differentiation, tumor development and tumor progression (35)(36)(37)(38). miRs, which regulate the expression of their target genes by base pairing with seed sequences in the 3'-UTR of mRNAs, have been shown to regulate the expression of Sp1 (39,40). In a previous study, miR-22 was reported to be downregulated in GC and inhibited cell proliferation, migration and invasion by targeting Sp1 (41).…”
Section: Discussionmentioning
confidence: 99%